Antologia tragedii greckiej - Aeschylus; Sophocles; Euripides; Stabryla, Stanislaw (Krakow : Wydawn. Literackie, 1989)
An anthology of classical Greek tradegies.
Ajschylosa Prometeusz w okawach.--Ajschylosa Oresteja.--Sofoklesa Krol Edyp.--Sofoklesa Antygona.--Eurypidesa Medea.--Eurypidesa Trojanki.
Keywords: Greek drama (Tragedy) -- Translations into Polish